PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA BANK UMUM KONVENSIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nyoria Anggraeni Mersa; Yulius Gessong Sampeallo; Retno Halimah (Politeknik Negeri Samarinda, 2021)
This research aims to analyze and prove the partial and simultaneous influence of the variables studied. This study used 3 independent variables. Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR) and Return on Asset (ROA), stock price was the dependent variable. The object of the research were Conventional commercial banks listed on the Indonesia Stock Exchange (IDX).The data in the study were obtained through the official website of the Indonesia Stock Exchange (www.idx.co.id) for the 2012-2019 period. The total data was 54 of 9 companies for 6 years. The analysis technique used the multiple linear regression by looking at the results of the SPSS output in the Standardized Coefficients Beta column. The results of multiple regression analysis using SPSS version 24 obtained the equation that was is Y= 0,310 + (-0,371) + 0,089 + (-0.090) + e. The result of multiple (Uji-t) showed that partially CAR had a positively and significant influence on the stock price, while the LDR variabel has a negative effect and significant value, and ROA and NPL variables have negative effect and not influence significant on the stock price. Meanwhile, the CAR, LDR, ROA and NPL variables simultaneously influence the stock price. Keywords: CAR, LDR, ROA, and NPL, Stock Price.